2010
DOI: 10.4319/lo.2010.55.6.2433
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of algal communities in the Lake of the Woods (Ontario, Canada) in response to turn‐of‐the‐century damming and recent warming

Abstract: Paleolimnological approaches were used to assess the ecological and environmental implications of diatom assemblage compositional changes recorded over the last , 200 yr from four sites in the Lake of the Woods (LoW), Ontario, Canada. Comparisons between a reference site (Whitefish Bay) and three disturbed sites (Bigstone Bay, Paleolimnological Project site No. 1, and Forrest Island) provide insights into the effects that multiple stressors (dam construction, total phosphorus [TP] changes, and recent warming) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 73 publications
4
62
0
Order By: Relevance
“…As a consequence of climate warming, the physical processes that lakes experience can be altered. Longer ice-free season and enhanced thermal stability, coupled with higher surface-water temperatures and the redistribution of nutrients within the water column, contribute to greater algal production within many lake ecosystems (38,39). Paleolimnological studies from a suite of lakes in Alberta (29,36) and the adjacent Northwest Territories (40) record notable shifts in lake primary production, influenced to some degree by climatic control.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of climate warming, the physical processes that lakes experience can be altered. Longer ice-free season and enhanced thermal stability, coupled with higher surface-water temperatures and the redistribution of nutrients within the water column, contribute to greater algal production within many lake ecosystems (38,39). Paleolimnological studies from a suite of lakes in Alberta (29,36) and the adjacent Northwest Territories (40) record notable shifts in lake primary production, influenced to some degree by climatic control.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have documented a series of possible climate-induced changes in boreal-region lakes, including a longer ice-free season [4][5][6][7], stronger or weaker thermal stratification [8,9], increased inputs of dissolved organic carbon and increased carbon burial [2,10], shifts in algal communities [1], and an increased frequency of cyanobacterial blooms [3]. These changes have been noted in remote lakes far removed from direct human disturbance, with the strongest evidence coming from the …”
Section: Introductionmentioning
confidence: 99%
“…Small diatoms and buoyant cyanobacteria have a distinct competitive advantage during periods of relative stability in lakes, as they experience reduced sinking velocities (Paerl, 1988;Winder et al, 2008) and may be able exploit subsurface habitats in the metalimnia of stratified lakes where nutrients are elevated (Fahnenstiel and Glime, 1983;Rühland et al, 2010). In our study, the deeper inland lakes showed evidence of weak to moderate stratification and, in at least one year (2001; described in Gunn and Snucins, 2010), strong thermal stratification has been observed in August in Hawley Lake.…”
Section: Discussionmentioning
confidence: 99%